Does Electricity Access Moderate The Effect Of Gender Inequality On Economic Growth? Panel Data Evidence From Asean Countries - Tarigan, Bumaman Teodeki; Syafii, Muhammad; Hasyim, Sirojuzilam; Ruslan, Dede (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study investigates whether electricity access moderates the relationship between gender inequality and economic growth in eight ASEAN countries (Indonesia, Cambodia, Lao PDR, Malaysia, Philippines, Singapore, Thailand, and Vietnam) during 1998–2023. Employing Panel Estimated Generalized Least Squares (EGLS) with Cross-Section Seemingly Unrelated Regression (SUR) as the primary method and Panel Corrected Standard Errors (PCSE) as the alternative, we analyze panel data comprising 208 observations. The dependent variable is GDP growth, while independent variables include the Gender Inequality Index (GII), Access to Electricity (ATE), and their interaction term (GII×ATE). Results from the Panel EGLS Cross-Section SUR model reveal that GII exhibits a negative but statistically insignificant effect on economic growth (coefficient = -4.377, p = 0.622), while ATE demonstrates a negative insignificant relationship (coefficient = -0.066, p = 0.208). The interaction term shows a positive but insignificant effect (coefficient = 0.016, p = 0.850), suggesting that electricity access does not significantly moderate the gender inequality-growth nexus in ASEAN countries during the study period. The PCSE model confirms these findings, indicating robustness of results. These findings contribute to understanding the complex interplay between gender equality, infrastructure development, and economic performance in Southeast Asian economies, offering implications for policymakers seeking to design integrated development strategies.